2023
DOI: 10.1021/acs.est.2c09163
|View full text |Cite
|
Sign up to set email alerts
|

Water Self-Purification with Zero External Consumption by Livestock Manure Resource Utilization

Abstract: Improper disposal of waste biomass and an increasing number of emerging contaminants (ECs) in water environment are universal threats to the global environment. Here, we creatively propose a sustainable strategy for the direct resource transformation of livestock manure (LM) into an innovative catalyst (Fe-CCM) for water selfpurification with zero external consumption. ECs can be rapidly degraded in this self-purification system at ambient temperature and atmospheric pressure, without any external oxidants or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…5 c, no signal of unpaired electrons was detected on GN, and a high intensity of unpaired electrons signal was detected on CoFeQds@GN-Nws, surpassing those observed in other comparative samples. Building upon our previous work, this result indicated that the lattice doping of Fe and Co completely changes the electron distribution on the catalyst, resulting in the formation of electron-rich Fe and Co micro-regions and electron-poor C(π) micro-regions in CoFeQds@GN-Nws [ [57] , [58] , [59] ]. The higher intensity of the unpaired electrons makes it easier for CoFeQds@GN-Nws to capture electrons from the pollutants during the reaction and facilitates the activation of DO.…”
Section: Resultssupporting
confidence: 59%
“…5 c, no signal of unpaired electrons was detected on GN, and a high intensity of unpaired electrons signal was detected on CoFeQds@GN-Nws, surpassing those observed in other comparative samples. Building upon our previous work, this result indicated that the lattice doping of Fe and Co completely changes the electron distribution on the catalyst, resulting in the formation of electron-rich Fe and Co micro-regions and electron-poor C(π) micro-regions in CoFeQds@GN-Nws [ [57] , [58] , [59] ]. The higher intensity of the unpaired electrons makes it easier for CoFeQds@GN-Nws to capture electrons from the pollutants during the reaction and facilitates the activation of DO.…”
Section: Resultssupporting
confidence: 59%
“…In these processes, inert pollutants can be confined and dissociated through the interactions with the surface EPC. Meanwhile, captured electrons are rapidly transferred to ERC through cation–π structures for dissolved oxygen (DO) reduction, thus achieving low-consumption water purification ( 23 , 24 ). However, the performance is still subject to some limitations in complicated environmental media, especially in the wastewater with high salinity ( 25 ).…”
mentioning
confidence: 99%
“…However, the performance is still subject to some limitations in complicated environmental media, especially in the wastewater with high salinity ( 25 ). Cation–π interaction is an essential noncovalent intermolecular binding force between cations (M + ) and electron-rich π orbitals ( 26 , 27 ), which can drive the microscopic electron transfer of π→M + (σ donation) or M + →π* (π back-donation) ( 23 , 26 ). It has been proved that interfacial confinement can fundamentally alter the energetics of cation–π-mediated assemblies ( 13 ).…”
mentioning
confidence: 99%
“…The coexisting anions and natural organic matter (e.g., humic acid, HA) in natural aqueous media usually have a negative impact on the purification efficiency of wastewater treatment technologies. 44 To investigate the potential applicability of the CaSO 3 /3D-Cu system in wastewater treatment, the effects of various background anions including CO 3 2− , Cl − , SO 4 2− , NO 3 − , and HA on TC degradation were explored. As displayed in Figure 6a, the addition of most anions (Cl − , SO 4 2− , and NO 3 − ) had little effect on the TC degradation in the CaSO 3 /3D-Cu system.…”
Section: Reaction Mechanism Of the Caso 3 /3d-cu System It Is Widely ...mentioning
confidence: 99%